Regional Development Overview : Challenges, Adopted Strategies, and New Initiatives - Jackson, Randall W (World Bank, Washington, DC, 2019)
Despite the increasing attention in recent years to the spatial dimensions of economic development, consideration of the importance of space and the recognition that macro, aspatial perspectives can prove to be misleading are not new. Around the world, much of the disappointment with the outcomes from spatial interventions may be traced to a lack of understanding of how regional economies work. This paper reviews the challenges that the consideration of regions brings into economic analysis. This work provides an overview of some of the key methods and tools that can be used to gain a better understanding of how regional economies work. The review aims to guide practitioners and analysts in the use of tools for regional economic analysis and inform discussion of the challenges regions face and the opportunities on which they can build.